2016
DOI: 10.2500/aap.2016.37.3980
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of oral immunotherapy with cow‘s milk and hen egg: A 10-year experience in controlled trials

Abstract: A careful review of the patients who received food OIT in controlled trials confirmed that AEs were not rare but that ∼90% of children could achieve an effective desensitization. The procedure remains investigational and should be performed only by trained physicians, especially in the pediatric setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The high frequency of allergic adverse reactions of the various approaches highlighted the need of refinements in the strategies. A careful review of the patients who received food oral immune therapy in controlled trials confirmed that adverse events were not rare but that ~90% of children could achieve an effective desensitization [ 53 ]. A promising strategy for preventing IgE cross-linking and thus enhancing safety of immune therapy, while still activating T cells, is the use of tolerogenic peptides [ 2 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The high frequency of allergic adverse reactions of the various approaches highlighted the need of refinements in the strategies. A careful review of the patients who received food oral immune therapy in controlled trials confirmed that adverse events were not rare but that ~90% of children could achieve an effective desensitization [ 53 ]. A promising strategy for preventing IgE cross-linking and thus enhancing safety of immune therapy, while still activating T cells, is the use of tolerogenic peptides [ 2 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Additional bigger, multicentric and randomized-controlled studies must answer multiple questions including optimal dose, ideal duration of immunotherapy, degree of protection, efficacy for different ages, severity and type of food allergy responsive to treatment [ 48 ]. The procedure remains investigational and should be performed only by trained physicians, especially in the pediatric setting [ 53 ]. Immunotherapy for food allergy is still not ready for the clinic, but current and upcoming studies are dedicated to collect enough evidence for the possible implementation of allergen-SIT as a standard treatment for food allergy [ 2 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The latter include also the following: uncontrolled or severe asthma; active malignant neoplasia(s); active systemic, autoimmune disorders; active eosinophilic esophagitis (EoE) or other gastrointestinal eosinophilic disorders; and initiation during pregnancy. Safety is a pivotal issue in any treatment [57][58][59]. Furthermore, in OIT, it is particularly important, as children are typically involved and potential adverse events are mostly immediate onset, food-induced IgE-mediated reactions, which can lead to anaphylaxis.…”
Section: Contraindications and Safetymentioning
confidence: 99%
“…[**21] Converserly, the rate of adverse events (AEs) during OIT largely varies in published studies but mild AEs are predominant and only a few dropped out for this reason. [**21] Unfortunately, reporting, description and grading of AEs are heterogenous and imprecise, and this makes it difficult to compare the real occurrence and severity of specific type of AEs among studies [57]. This drawback also affects the identification of risk factors and their avoidance.…”
Section: Contraindications and Safetymentioning
confidence: 99%
“…With regard to the safety of oral immunotherapy, Pajno et al 27 described the occurrence and characteristics of adverse events with oral immunotherapy, based on their experience conducting controlled trials in children with milk and egg allergies. The authors reported that adverse events are not rare but that ϳ90% of children can achieve an effective desensitization.…”
mentioning
confidence: 99%